Developing Plant Cultivation Technologies for Space at DLR - From Antarctica to the Moon - Franke, Michel Fabien (2024)
By signing the Artemis Accords, spacefaring nations from around the globe have expressed their willingness to return astronauts to the Moon by the end of this decade. Unlike past lunar programs, Artemis aims to establish a long-term human presence on the surface of Earths natural satellite. A crewed outpost like the Artemis Base Camp requires a reliable supply of food and other consumables like oxygen. To address this need in a sustainable way, frequent resupply from Earth is not an option. Instead, a closed-loop bio-regenerative life-support system (BLSS) will be needed to produce fresh food and oxygen on-site, while eliminating carbon dioxide and other unwanted waste products. Thus, BLSS technologies have to be developed and field-tested in a space-analogue environment. To this end, DLR has founded the Planetary Infrastructures research group. The group has worked on BLSS for more than 10 years and has developed, built and operated the prototype-level greenhouse for space called EDEN (Evolution & Design of Environmentally-closed Nutrition-Sources) ISS at the German Neumayer-Station III in Antarctica. The purpose of this facility was to enable multidisciplinary research on topics related to plant cultivation on future human space exploration missions. Research on plant health monitoring, microbiology, food quality and safety, and human factors was conducted, while simultaneously validating the system. After 5 years in Antarctica and more than 1 ton of biomass produced, the greenhouse was shipped back to Germany, bringing the project to a successful end in 2023. The follow-on project, EDEN LUNA, is currently under development. Its goal is to refurbish and upgrade the existing Controlled Environmental Agriculture (CEA) subsystems, while also introducing new technologies like a robotic arm, nutrient recovery from urine, and AI-based risk mitigation. Additionally, the group is working on a realistic version of a Lunar Agriculture Module Ground Test Demonstrator (LAM-GTD) together with the Canadian Space Agency ...